Relationship between Emotional Distress and Workplace Influence on Depressive Symptoms among Online Motorcycle Taxi Drivers - Lie Tanu Merijanti; Nany Hairunisa; Alvin Muhamad Ridwan; Pusparini Pusparini; Meiyanti Meiyanti; Muljadi Tjahjadi; Marzuki bin Isahak (Althea Medical Journal)
Background: The rise of online motorcycle taxi services, driven by the demand for transportation and new technologies, has created a new landscape for drivers. However, despite the benefits, these drivers are not considered employees and are therefore vulnerable to psychosocial risks. This study aimed to investigate the relationship between psychosocial hazards and depressive symptoms among online motorcycle taxi drivers.